Expression Pattern and Promoter Analysis of a Eucalyptus grandis Germin-like Gene - Sassaki, Flavio T. [UNESP]; Bravo, Juliana P. [UNESP]; Gonzalez, Esteban R.; Maia, Ivan G. [UNESP] (Springer, 2015)
Germin-like proteins (GLP) have been implicated in multiple physiological processes in plants, but our understanding of their functional roles, especially in trees, is far from complete. In the present study, an expressed sequence tag (EST) encoding a putative leaf-specific GLP was selected in silico using an expression-profile data from eucalyptus. Corroborating the in silico prediction, the expression of the corresponding gene (named EgGLP) in leaves of Eucalyptus grandis was validated using reverse transcription-PCR. Spatial EgGLP expression patterns were further investigated using a promoter-beta-glucuronidase (GUS) reporter gene fusion. In E. grandis seedlings, the EgGLP promoter was able to modulate transient GUS expression in the cotyledons, while in stably transformed tobacco plants, reporter expression was predominantly observed in the shoot apical meristem and in leaf vasculature. Phylogenetic analysis revealed that EgGLP belongs to subfamily III and is closely related to GLPs known to be regulated by the circadian rhythm. In this context, we show that the activity of the EgGLP promoter in tobacco is modulated by light/dark transition.
Keywords: Eucalyptus grandis; Germin-like protein; Promoter region; Leaf expression Nicotiana tabacum